Microtribological behavior of metal-matrix nanocomposites based on the nanocontainer-like layered oxides - Alexander S. Logvinovich; Tatsiana V. Sviridova; Dmitri V. Sviridov; Alexei V. Kaparikha (Журнал Белорусского государственного университета: Химия, 2018)
The electrochemical codeposition of nickel with the dispersed molybdenum oxide of layered structure yields metalmatrix composites in which the second phase is capable to play a role of container retaining organics in its internal volume. It is shown that the intercalation of benzotriazole (a well-known corrosion inhibitor) into the interlayer volume of MoO3 ensures an effective suppression of tribocorrosion of matrix metal.